2006
DOI: 10.1007/s00438-006-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and phylogenetic context for conglutin genes in Arachis based on genomic sequence

Abstract: Comparative genomic and cDNA sequence analysis of ara h 2, a major peanut allergen, and a related conglutin ara h 6 were performed in Arachis hypogaea L. and its putative progenitors, Arachis duranensis and Arachis ipaensis. The complete identity between sequences encoding Ara h 2 isoforms demonstrated that these are homeologous genes and represent orthologs from diploid ancestors. Three copies of ara h 6 were identified in A. hypogaea, one of them located in the A-genome and the other two in the B-genome. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 50 publications
(68 reference statements)
2
51
0
Order By: Relevance
“…13), makes the assembly of the peanut genome sequence very challenging. However, the A and B subgenomes appear to have undergone relatively few changes since polyploidization: genomic in situ hybridization (GISH), using genomic DNA from the diploid species as probes, clearly distinguishes A and B chromosomes and does not show large A-B mosaics 7,8 . Also, the genome size of A. hypogaea is close to the sum of those for A. duranensis and A. ipaensis (1.25 and 1.56 Gb, respectively 14 ), indicating that there has been no large change in genome size since polyploidy.…”
Section: Openmentioning
confidence: 99%
“…13), makes the assembly of the peanut genome sequence very challenging. However, the A and B subgenomes appear to have undergone relatively few changes since polyploidization: genomic in situ hybridization (GISH), using genomic DNA from the diploid species as probes, clearly distinguishes A and B chromosomes and does not show large A-B mosaics 7,8 . Also, the genome size of A. hypogaea is close to the sum of those for A. duranensis and A. ipaensis (1.25 and 1.56 Gb, respectively 14 ), indicating that there has been no large change in genome size since polyploidy.…”
Section: Openmentioning
confidence: 99%
“…These additional 12 amino acids in Ara h 2.02 corresponded to the difference in molecular mass of the two Ara h 2 bands found on SDS-PAGE (Chatel et al, 2003). Recently, it was shown that these isoforms are homeologous genes that are orthologs, each derived from one of the diploid ancestors of peanut (Ramos et al, 2006).…”
mentioning
confidence: 91%
“…Because of the extent and seriousness of hypersensitive reactions, these allergens and associated genes are being intensely studied to identify specific epitopes, to develop detection methods in foods, and to develop strategies to reduce hypersensitivity to peanut [45]. Research to reduce peanut allergenicity by manipulation of the peanut genome is in progress [43].…”
Section: Introductionmentioning
confidence: 99%